EFFORTS BY ISLAMIC RELIGIOUS EDUCATION TEACHERS TO SUPPORT STUDENTS FROM BROKEN HOMES AT SMP TAKHASUS AL-QUR’AN KALIBEBER, MOJOTENGAH, WONOSOBO - Eli Fitriana; Nasokah; Sofan Rizqi (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims to: 1) understand the perspectives of Islamic Religious Education (PAI) teachers regarding students from broken homes; 2) identify the efforts made by PAI teachers to support students from broken homes at SMP Takhasus Al-Qur’an Kalibeber, Wonosobo; and 3) determine the factors that facilitate or hinder these teachers' efforts. This study employs a qualitative method, specifically a narrative research design. Qualitative research eschews statistics in favor of a naturalistic approach to gain an in-depth understanding of phenomena. Data collection relies on three techniques: observation, interviews, and documentation. Primary data were obtained directly from the research subjects through in-depth interviews, while secondary data were gathered from various documentary sources, such as photographs and statistical records. Motivated by compassion and religious values, PAI and Guidance and Counseling (BK) teachers at SMP Takhasus Al-Qur’an Kalibeber, Wonosobo, work hand-in-hand to support students from broken homes. Their holistic approach akin to a warm blanket encompasses special attention, positive encouragement, and religious insights from PAI teachers, alongside individual counseling, support groups, and parent involvement facilitated by BK teachers. However, their journey is not without challenges. While facilitating factors such as teacher expertise, collaboration, school support, and student awareness exist and can be further optimized, obstacles including limited resources, social stigma, the complexity of issues, and a lack of training must be overcome.Consequently, PAI teachers need to foster close collaboration with various stakeholders and commit to continuous professional development. In doing so, their efforts to assist students from broken homes can become more effective and yield significant positive impacts, serving as a ray of sunshine that illuminates a brighter future for these students.